2015
DOI: 10.7314/apjcp.2015.16.14.5875
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Oxidative Metabolism Related Genes in Cholangiocarcinomas

Abstract: Cholangiocarcinoma (CCA) is a rare but highly fatal cancer for which the molecular mechanisms and diagnostic markers are obscure. We therefore investigated the kinetic expression of isocitrate dehydrogenase-1 (IDH1), isocitrate dehydrogenase-2 (IDH2) and homogentisate 1,2-dioxygenase (HGD) during the tumorigenesis of O. viverrini infection-associated CCA in an animal model, and confirmed down-regulation of expression in human cases of opisthorchiasis-associated CCA through real time PCR. Kinetic expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The HGD gene encodes one of the enzymes called homogentisate 1,2 dioxygenase, which is required for the catabolism of the amino acids tyrosine and phenylalanine and is generally active in the kidneys and liver to catalyze oxidation-reduction reactions. The current study showed that high HGD mRNA expression (≥ 3-fold) was associated with poorer survival of, histological grade, advanced stage, and metastasis of cholangiocarcinoma patients [29]. Previous results have shown that HGD is a potential key factor in the regulatory mechanism of BRAFV600E-mediated PTC.…”
Section: Discussionsupporting
confidence: 58%
“…The HGD gene encodes one of the enzymes called homogentisate 1,2 dioxygenase, which is required for the catabolism of the amino acids tyrosine and phenylalanine and is generally active in the kidneys and liver to catalyze oxidation-reduction reactions. The current study showed that high HGD mRNA expression (≥ 3-fold) was associated with poorer survival of, histological grade, advanced stage, and metastasis of cholangiocarcinoma patients [29]. Previous results have shown that HGD is a potential key factor in the regulatory mechanism of BRAFV600E-mediated PTC.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, EIF5A2 regulates the resistance of gastric cancer cells to cisplatin by mediating epithelial-stromal transformation (Sun et al, 2018). The downregulation of HGD expression was found to be associated with less metastasis, as well as better prognosis, pathological grade, and clinical stage of cholangiocarcinoma patients (Aukkanimart et al, 2015). The PLS1 was overexpressed in CRC patients and associated with lymph node metastasis and a poor prognosis.…”
Section: Discussionmentioning
confidence: 87%